Gerak Seru Anak TK YLPI Marpoyan - Apriani, Leni; Alpen, Joni; Fatmawati; Yulianti, Mimi; Habibah, Zahratul; Dari, Putri Yulan (Community Education Engagement Journal, 2025)
The “Gerak Seru Anak TK” program was implemented to improve the gross motor skills of early childhood children. The main problems identified were low levels of physical activity among children due to limited facilities, academic dominance, and a lack of understanding among teachers. Activities were carried out through preparation, implementation, and evaluation stages using a fun physical play approach, such as cheerful fitness exercises, ball relays, and catch and throw games. The results of the activities showed an improvement in children's coordination, balance, and agility, as well as an increase in teachers' skills in designing movement activities. In addition, parents became more aware of the importance of physical activity for children. This program has proven to be effective in promoting the holistic development of early childhood through healthy and fun games.